Sustainable food production in Africa: turning African Countries into development catalysts, food reservoirs and exporters - Oyekanmi, E.; Coyne, D.; Fawole, B.; Adeoye, G. (2020)
The myriad of challenges facing Africa, were considered in this paper, which include the nagging triplet problems of poverty, hunger and diseases. Africa is prominent in the world hunger map of Food and Agriculture Organization. Therefore, this paper identified poorly tapped natural and human resources, uneconomically viable policies and poor management as some of the banes of Africa’ setback. This work proffered proactive solutions to freeing Africa from the triplet perennial problems of poverty, hunger and diseases, through intervention in the area of sustainable organic agricultural food production geared towards wealth creation in an integrated community based agriculture. Organic agriculture gives credence to good health, thus is a viable instrument in freeing Africa from diseases. In this paper, the abundance of agrarian ecologies and resources domiciled in Africa, were highlighted and put forth to be harnessed for moving the continent from the present precarious predicament to an enviable status. Empirical information presented in this paper recommended organic agriculture as the panacea to sustainable food production, improved health of the populace, conducive environmental condition and for solving the problem of climate change. Organic agriculture will also facilitate the establishment of bilateral trade agreements, thus boosting foreign earnings of African countries. This will make other nations of the world to be heavily dependent on Africa for raw materials and export of high quality organic food to feed the world. The multiplier effects of these coordinated activities will turn African countries into development catalysts, food reservoirs and enhanced foreign exchange earners.